me pueden ayudar con los q mas puedan se los agradesco!!

1+sec(x) sen^2(x)

------------- = ------------

sec(x) 1-cos(x)

(1-tan(x))(1-cot(x))= 2-sec(x)csc(x)

sen(2x)

--------------- = tan(x)

1+cos(2x)

tan(x/2) = csc(x)- cot(x)

1+tan(x) tan (x/2) = sec(x)

sen(3x)+cos(3x)

------------------------ = 1+2sen(2x)

cos(x)-sen(x)

( cos(x/2) -sen(x/2))^2 = 1-sen(x)

cos(3x)-cos(7x)

----------------------- = tan(2x)

sen(3x)+sen7x)

1

Respuestas

2012-08-21T16:28:33+02:00

(1-tan(x))(1-cot(x))= 2-sec(x)csc(x)

(1-sen/cos)(1+sen/cos)

2-secx csc